PROSPECTS OF THE DEVELOPMENT OF CRITERIA FOR ASSESSING THE QUALITY OF EDUCATION OF STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS (American Journal of Pedagogical and Educational Research, 2023)
The article describes the principles of the competence development model of university students studying under the credit-modular system. In addition, the structure of improving the quality of the educational system was developed by the author as a model for organizing students' classes.